Does Islam impede development? A critical analysis. Issue 5 (14th October 2019) - Sidani, Yusuf
Abstract : Purpose: This paper aims to investigate the relationship between Islam and economic underdevelopment that characterizes many Muslim societies. It examines the Weberian thesis regarding Islam and development, assessing the role of Islamic law, in addition to the concepts of rationality and fatalism. Design/methodology/approach: The paper reviews the major theses regarding the link between Islam and development and makes an attempt at explaining economic underdevelopment by engaging the most prominent arguments in this regard. Findings: Lack of development in most Muslim societies is a multidimensional problem, and it would not help to rely on explanations that are culturally deterministic or sociologically reductionist. Practical implications: Development requires improvements at various regulatory, economic, educational, and social levels. It also requires a significant transformation in people's value systems that guide their actions. This requires a process of self-examination, not only looking at exogenous factors to explain failures, but also to focus on one's own responsibility to alleviate crisis situations. Originality/value: This paper challenges many of the for-granted theses regarding the purported link between Islam and development. While not dispelling the need for internal reflection for Muslim societies, it puts some of the popular arguments regarding this link in proper perspective.